Current clinical practice in adapted automated peritoneal dialysis (aAPD)-A prospective, non-interventional study - Vera, Manel; Cheak, Bee Boon; Chmelíčková, Hana; Bavanandan, Sunita; Goh, Bak Leong; Abdul Halim, Abdul Gafor; Garcia, Isabel; Gajdoš, Martin; Alonso Valente, Rafael; De Los Ríos, Tatiana; Atiye, Saynab; Stauss-Grabo, Manuela; et al. (PLoS One, 2021)
Adapted automated peritoneal dialysis (aAPD), comprising a sequence of dwells with different durations and fill volumes, has been shown to enhance both ultrafiltration and solute clearance compared to standard peritoneal dialysis with constant time and volume dwells. The aim of this non-interventional study was to describe the different prescription patterns used in aAPD in clinical practice and to observe outcomes characterizing volume status, dialysis efficiency, and residual renal function over 1 year. Prevalent and incident, adult aAPD patients were recruited during routine clinic visits, and aAPD prescription, volume status, residual renal function and laboratory data were documented at baseline and every quarter thereafter for 1 year. Treatments were prescribed according to the nephrologist's medical judgement in accordance with each center's clinical routine. Of 180 recruited patients, 160 were analyzed. 27 different aAPD prescription patterns were identified. 79 patients (49.4%) received 2 small, short dwells followed by 3 long, large dwells. During follow-up, volume status changed only marginally, with visit mean values ranging between 1.59 (95% confidence interval: 1.19; 1.99) and 1.97 (1.33; 2.61) L. Urine output and creatinine clearance decreased significantly, accompanied by reductions in ultrafiltration and Kt/V. 25 patients (15.6%) received a renal transplant and 15 (9.4%) were changed to hemodialysis. Options for individualization offered by aAPD are actually used in practice for optimized treatment. Changes observed in renal function and dialysis efficiency measures reflect the natural course of chronic kidney disease. No safety events were observed during the study period.
Keywords: Kidney Function Tests; vyšetření funkce ledvin; Aged; lidé středního věku; senioři; lidé; Adult; Middle Aged; Prospective Studies; dospělí; následné studie; prospektivní studie; chronické selhání ledvin; Female; peritoneální dialýza; Male; ženské pohlaví; Humans; mužské pohlaví; Follow-Up Studies; Peritoneal Dialysis; Kidney Failure, Chronic